4(3n+3)=9(9n+1)+5

Simple and best practice solution for 4(3n+3)=9(9n+1)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3n+3)=9(9n+1)+5 equation:


Simplifying
4(3n + 3) = 9(9n + 1) + 5

Reorder the terms:
4(3 + 3n) = 9(9n + 1) + 5
(3 * 4 + 3n * 4) = 9(9n + 1) + 5
(12 + 12n) = 9(9n + 1) + 5

Reorder the terms:
12 + 12n = 9(1 + 9n) + 5
12 + 12n = (1 * 9 + 9n * 9) + 5
12 + 12n = (9 + 81n) + 5

Reorder the terms:
12 + 12n = 9 + 5 + 81n

Combine like terms: 9 + 5 = 14
12 + 12n = 14 + 81n

Solving
12 + 12n = 14 + 81n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-81n' to each side of the equation.
12 + 12n + -81n = 14 + 81n + -81n

Combine like terms: 12n + -81n = -69n
12 + -69n = 14 + 81n + -81n

Combine like terms: 81n + -81n = 0
12 + -69n = 14 + 0
12 + -69n = 14

Add '-12' to each side of the equation.
12 + -12 + -69n = 14 + -12

Combine like terms: 12 + -12 = 0
0 + -69n = 14 + -12
-69n = 14 + -12

Combine like terms: 14 + -12 = 2
-69n = 2

Divide each side by '-69'.
n = -0.02898550725

Simplifying
n = -0.02898550725

See similar equations:

| (x-(8/x))^2-5(x-(8/x))-14=0 | | 12x-127=4x+169 | | (8x^4-2x^2+3x-5)-(2x^4+x^3+3x+5)= | | (3x+3)+(15-3x)= | | 7(2n+2)=7(7n+7)+9 | | 4(q)+(-1)(1-q)=1(q)+2(1-q) | | -4n(6n-5)+3n= | | 5(x+3)=4x+14 | | 0.9x-5.3=0.1 | | (9x-6)+6= | | 2+-6m=-4m+10 | | -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 | | 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b |

Equations solver categories